Physical Fitness Leads to Risk of Delayed Onset Muscle Soreness in the Lower Extremities of Sangsekarta Dancers, Malang - Najah Fadiya Humaira; Bayu Prastowo; Safun Rahmanto; Syi’ar Aprilla Tanazza (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2024)
Low physical fitness and high dance intensity cause eccentricity, leading to microscopic damage to muscle fibers. That condition leads to an inflammatory response, pain, or Delayed Onset Muscle Soreness (DOMS). It is a condition in which muscle soreness occurs after a high-intensity activity that occurs after 24-48 hours. This study aims to see the relationship between physical fitness and the risk of lower extremity DOMS in dancers registered in KEPK-FKUMM with the ethical number E.5.a/042/LEPK-UMM/II/2024. The research method used an analytical observational design with a cross-sectional study approach. The research respondents consisted of 62 dancers out of a total of 120 based on the purposive sampling technique. Inclusion criteria included traditional and modern dancers who had practiced 2 days before the study. Meanwhile, the exclusion criteria were dancers in the rehabilitation or injury phase. Data testing using correlation analysis with a p-value of <0.001 (p<0.05) means a significant relationship exists between physical fitness and the risk of lower extremity DOMS in dancers. The coefficient value of -0.731 indicates a strong relationship. The coefficient value means that the higher a person's physical fitness, the lower the level of DOMS.